Determining the vending machine purchasing experience towards customer satisfaction among university students / Mimi Nadhirah Aszhar and Muhammad Amirul Firdaus Asri - Aszhar, Mimi Nadhirah; Asri, Muhammad Amirul Firdaus (2021)
The usage of the vending machine has become a significant thing in the food industry nowadays. The vending machines provide many benefits for customers especially for students. It can provide convenient, independent services for customers and is accessible 24 hours a day, and seven days a week. Thus, the presence of a vending machine on the university campus becomes convenient for students. The primary goal of this research is to determine the relationship between the purchasing experiences that may contribute to customer satisfaction among the university students towards vending machines and to identify the most influential determinants affecting vending machine purchasing experience and customer satisfaction among the university students. This study assessed the following five determinants: mode of payment, vending machine condition, vending machine maintenance, product assortment, and product freshness. The convenience sampling technique was used to collect data from 364 customers in the UiTM Terengganu campus using Likert-scale questionnaires via the online survey.